Efek Variasi Temperatur Kalsinasi Terhadap Kandungan Senyawa Silika Dari Lumpur Teluk Kendari Dengan Menggunakan X-Ray Flourescence (XRF) - Humarli, Debby Enjelica; Anas, Muhammad; Rufa Mongkito, Vivi Hastuti (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to determine the effect of calcination temperature variations on the content of silica compounds. This research was conducted in stages, namely taking samples from the Kendari Bay clay then the samples were washed with clean water and distilled water then filtered and dried in the sun for 24 hours. After drying, the sample was crushed and sieved with a 60 mesh sieve, after that it was leached by the solid-liquid extraction method with 6 M HCl solution, stirred using a magnetic stirrer at a temperature of 100°C for 5 hours. then the sample is filtered to obtain a precipitate then soaked with distilled water until the pH of the water is neutral and dried in an oven at a temperature of 100°C for 4 hours and calcined with temperature variations of 300°C, 500°C, 700°C and 900°C. In this study, X-ray Flourescence (XRF) was used to determine the content of silica compounds in Kendari Bay clay. The results showed that samples without calcination had a lower content of silica compounds compared to samples calcined with variations in temperature. The results obtained were 72.95% without calcination, while the calcination with temperature variations of 300°C, 500°C, 700°C and 900°C resulted in 76.31%, 77.18%, 77.00% and 78.98% respectif. Based on the results obtained, it can be concluded that the calcination temperature variations can affect the purity levels of silica contained in Kendari Bay clay.